New frame for an old issue: How organizations view frame choice, embedding, and efficacy about child, early, and forced marriage. - Murdie, Amanda; Calhoun, Morgan; Park, Baekkwan; Hart, Jacqueline; Mullinax, Margo (Journal of Human Rights)
What leads those working on the front lines of a problem to adopt a particular advocacy frame? How does a frame of an issue or problem affect the day-to-day work of nongovernmental organizations (NGOs) and advocates? Focusing on framing regarding child, early, and forced marriage (CEFM), we build a unique argument that examines both frame change and frame embedding within advocacy organizations. Frame adoption is not a dichotomous decision but a continuous process, with varying degrees to which a frame can be identified with, adopted, and embedded into an organization. Our argument suggests that the degree of frame embedding cannot come strictly from above or outside the organization; work by donors and outside actors may be able to encourage lip-service to a new frame but will not, on their own, lead to the full adoption and embedding of a frame in a way that is critical for problem-solving. We test the implications of our argument using a new dataset based on the responses of 1,118 global advocates working on CEFM. Our project is not only the first large-scale survey of CEFM advocates but also one of the first large-scale surveys of advocates and NGOs in general.